Analisis Pemilihan Penolong Persalinan - Siska Dhewi (Faletehan Health Journal, 2022)
In Indonesia, birth delivery assistance that utilizes health workers especially midwives by birthing mothers is still very low when compared to the health indicators determined by the government. A birthing mother has a high death risk when the delivery process is assisted by non-skilled and trained health workers. This study aimed to analyze the factors related to the selection of birth attendant. The research design was cross-sectional and the sample size was 43 respondents. The results of the bivariate analysis showed that there was a correlation between age (p value = 0.012), parity (p value = 0.030), delivery costs (p value = 0.002), and ease of access (p value = 0.000) with the selection of birth attendant. Local health agencies were required to be able to improve better health facilities and more intensively increase public awareness in choosing skilled and trained health workers as birth attendant.